Juegos lúdicos en el desarrollo de la creatividad de los niños de 4 años de edad - Gomez Anchundia, Nayely Dalay (2023)
This Project has the purpose of carrying out the development and creativity of the student, the game is a fundamental activity for the development and learning of children, since it allows them to enhance their imagination, explore the environment in which they operate , express their particular vision of the world, manifesting it through their creativity through oral and body language, and the development of socio-emotional and psychomotor skills that materialize from their relationship between peers and adults. More than just an opportunity to have fun, play enriches the child's brain, body and life in a very important way, since it affects their development and healthy growth. Playing improves in our little ones their ability to plan, organize, relate and regulate their emotions. Recreational games were developed such as: free, traditional, directed, competitive play and group dynamics with which motor development, lateralization, coordination, balance, space, location in space, rhythm, self-control are achieved. The contribution of new activities in motor development will serve as a guide for teachers and the institution, as a basis in initial education in which children build their autonomy, identity and self-esteem. In this investigation the methods used were used: Inductive, Deductive and problematic; Since it is a rational, systematic and logical process, the types of research were bibliographic, field, descriptive and diagnostic because it is directed to the situation of the variables; The research level is correlational, descriptive because it analyzes and evaluates the relationship of the variables. For the data collection, we worked with the observation technique, through the observation sheet instrument, solutions were proposed to meet the expectations in improving the initial stage with approaches and new initiatives that strengthen the training process as the fundamental pillar in the educational field, taking the game as a daily practice in which skills that will serve children throughout their lives are fostered.